Autosomal dominant Emery-Dreifuss muscular dystrophy caused by a mutation in the lamin A/C gene identified by exome sequencing: a case report - Kristy Iskandar; Sunartini; Farida Niken Astari; Rizki Amalia Gumilang; Nissya Ilma; Ni Putu Shartyanie; Guritno Adistyawan; Grace Tan; Gunadi; Poh San Lai (BMC, 2022)
Abstract Background Emery-Dreifuss Muscular Dystrophy (EDMD) is an uncommon genetic disease among the group of muscular dystrophies. EDMD is clinically heterogeneous and resembles other muscular dystrophies. Mutation of the lamin A/C (LMNA) gene, which causes EDMD, also causes many other diseases. There is inter and intrafamilial variability in clinical presentations. Precise diagnosis can help in patient surveillance, especially before they present with cardiac problems. Hence, this paper shows how a molecular work-out by next-generation sequencing can help this group of disorders. Case presentation A 2-year-10-month-old Javanese boy presented to our clinic with weakness in lower limbs and difficulty climbing stairs. The clinical features of the boy were Gower's sign, waddling gait and high CK level. His father presented with elbow contractures and heels, toe walking and weakness of limbs, pelvic, and peroneus muscles. Exome sequencing on this patient detected a pathogenic variant in the LMNA gene (NM_170707: c.C1357T: NP_733821: p.Arg453Trp) that has been reported to cause Autosomal Dominant Emery-Dreifuss muscular dystrophy. Further examination showed total atrioventricular block and atrial fibrillation in the father. Conclusion EDMD is a rare disabling muscular disease that poses a diagnostic challenge. Family history work-up and thorough neuromuscular physical examinations are needed. Early diagnosis is essential to recognize orthopaedic and cardiac complications, improving the clinical management and prognosis of the disease. Exome sequencing could successfully determine pathogenic variants to provide a conclusive diagnosis.